Sex, grade-level and stream differences in learning environment and attitudes to science in Singapore primary schools - Peer, J.; Fraser, Barry (Kluwer Academic Publishers, 2015)
Learning environment research provides a well-established approach for describing and understanding what goes on in classrooms and has attracted considerable interest in Singapore. This article reports the first study of science classroom environments in Singapore primary schools. Ten scales from the What Is Happening In this Class?, Constructivist Learning Environment Survey and Test Of Science Related Attitudes were administered to 1,081 students in 55 classes. Factor and reliability analyses provided strong support for this widely-applicable questionnaire for assessing Involvement, Teacher Support, Investigation, Task Orientation, Cooperation, Personal Relevance, Uncertainty, Student Negotiation, Attitude to Inquiry and Enjoyment of Science Lessons among Singaporean primary-school students. Statistically significant findings of small magnitude emerged for sex differences, grade-level differences, stream differences, the stream–by–sex interaction and the grade–by–stream interaction.